Integrated Land Registration System: Between Legal Certainty and Challenges (Case of Semarang City) - Rachmawati, Fairus Augustina; Choirinnisa, Shafa Amalia; Latif, Latif (Indonesian Journal of Advocacy and Legal Services, 2021)
In providing legal certainty for the control and ownership of community land parcels, the government carries out a program of registration and data collection of land parcels or what is called Complete Systematic Land Registration (PTSL). In its implementation, the city government of Semarang is targeting as many as 50,000 certificates to be registered with a total of 55,000 land parcels so that with a high quantity output, many problems will occur and a strategy is needed to solve it. Based on these problems, it is necessary to study related problems and the completion of the Semarang City PTSL Program 2021. The research was carried out using a juridical approach by obtaining the results of research in the field. Especially in the area of ​​Bendan Duwur and Sampangan urban villages, Semarang City in implementing the PTSL program in 2021 in the City of Semarang. Through this research, the obstacles to implementing PTSL Semarang City 2021 lie in the implementation of socialization, data collection and asset registration as well as in digitizing PTSL data. The settlement strategy that can be taken to minimize the problems of implementing PTSL is by improving resource strategies, coordinating with villages / sub-districts in making a Physical Land Acquisition Statement, as well as educating the public regarding online data that has been undertaken to support conversion from analog data to data digital.